Biología reproductiva de la cascabel centroamericana Crotalus durissus durissus (Serpentes: Viperidae) en Costa Rica - Solórzano, Alejandro; Cerdas, Luis (Revista de Biología Tropical, 1988)
In Costa Rica, rattlesnakes mate during the early dry season (December and January) and births occur in the early rainy season (May-July). Gestation is therefore about 6 months. The mean number of offspring is 22.9 and is significantly correlated with the size of the female. Newborn rattlesnakes are 27,543.0 cm in length and weight 11.4 - 46.3 g. They are relatively docile. Adult males are longer and heavier than females. Females seem to have their first litter when their size exceeds 120 cm.